Multiple access ethernet passive optical network testbed - Sadon S.K.; Din N.M.; Radzi N.A.; Yaacob M.B.; Maier M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bandwidth; Frequency allocation; Local area networks; Optical communication; Passive networks; Passive optical networks; Personal computers; Testbeds; DBA; Design parameters; Dynamic bandwidth allocation; EPON; Ethernet passive optical networks; Open-source network; Prolog; Traffic management; Ethernet